1999
DOI: 10.1016/s0893-133x(98)00087-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 5-HT2C/2B Antagonist SB 206553 on Hyperactivity Induced by Cocaine

Abstract: The behavioral effects of cocaine in rodents include the stimulation of locomotor activity and stereotypy as well as convulsions at higher doses (Scheel-Kruger et al. 1977;McCreary and Marsden 1993). Cocaine also serves as a positive reinforcer for operant behavior (de Wit and Wise 1977) and elicits interoceptive stimulus effects easily discriminable from saline . The locomotor stimulant effects have been linked to the inhibition of dopamine (DA) reuptake (Koe 1976) and a subsequent enhancement of DA activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 31 publications
5
41
3
Order By: Relevance
“…Both pharmacological blockade of the 5-HT 2C receptor (McCreary and Cunningham, 1999;Fletcher et al, 2002), as well as elimination of the expression of this receptor through 5-HT 2C receptor gene deletion (Rocha et al, 2002), can enhance the stimulant and reinforcing effects of cocaine. This suggests that the expression of the behavioral effects of cocaine may depend to some extent upon the endogenous tone of 5-HT acting upon this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Both pharmacological blockade of the 5-HT 2C receptor (McCreary and Cunningham, 1999;Fletcher et al, 2002), as well as elimination of the expression of this receptor through 5-HT 2C receptor gene deletion (Rocha et al, 2002), can enhance the stimulant and reinforcing effects of cocaine. This suggests that the expression of the behavioral effects of cocaine may depend to some extent upon the endogenous tone of 5-HT acting upon this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of 5-HT 2A or 5-HT 2C receptors had opposite effects on cocaine-induced locomotor activity. Thus, 5-HT 2A receptor blockade with M100,907 attenuated cocaine-induced locomotion, whereas 5-HT 2C blockade with SB 242084 or SB 206553 enhanced cocaine-induced activity [216,[218][219][220]. It has been found that RO 60-0175 reduces cocaine-reinforced behaviour by stimulating 5-HT 2C receptors [221].…”
Section: -Ht 2c Receptors and Drug Of Abusementioning
confidence: 99%
“…During recent years, numerous studies have focused on the role of the serotonergic2C receptor (5-HT 2C R) in the modulation of this DA pathway and its potential to control cocaine dependence (Bubar and Cunningham, 2006;Di Matteo et al, 2002;Higgins and Fletcher, 2003). Indeed, 5-HT 2C Rs are densely localized in brain regions containing DA cell bodies (VTA) and terminals (NAc) (Bubar and Cunningham, 2006;Clemett et al, 2000;Pazos et al, 1985;Pompeiano et al, 1994), and are known to modulate DA-dependent behavioral and neurochemical effects induced by cocaine (Fletcher et al, 2002(Fletcher et al, , 2006Grottick et al, 2000;McCreary and Cunningham, 1999;Navailles et al, 2004). Specifically, the systemic administration of the 5-HT 2C R agonist Ro 60-0175, and the 5-HT 2C R antagonist SB 242084 has been shown to respectively inhibit and potentiate cocaineinduced behaviors including its hypermotive and rewarding effects (Fletcher et al, 2002(Fletcher et al, , 2006Grottick et al, 2000).…”
Section: Introductionmentioning
confidence: 99%